1989
DOI: 10.1073/pnas.86.7.2453
|View full text |Cite
|
Sign up to set email alerts
|

Microbial glycolipids: possible virulence factors that scavenge oxygen radicals.

Abstract: Two important pathogens of developing countries, Mycobacteium leprae, the etiologic agent of leprosy, and Leishmania donovani, the protozoal parasite that causes kalaazar, persist in the human host primarily in mononuclear phagocytes. The mechanims by which they survive in these otherwise highly cytocidal cells are presently unknown. Since the best understood cytocidal mechanism of these cells is the oxygen-dependent system that provides lethal oxidants including the superoxide anion (O-), hydrogen peroxide (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
124
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(125 citation statements)
references
References 24 publications
1
124
0
Order By: Relevance
“…It has been implicated in several processes at different steps of the infection cycle: tropism for Schwann cells or phagocytes; the resistance of the leprosy bacillus to intracellular killing; and immunomodulatory activities (18,50,14). However, analysis of the contribution of PGL-1 to the pathogenicity of M. leprae has been hampered by the failure of the bacterium to grow on laboratory media and its extremely slow growth in animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been implicated in several processes at different steps of the infection cycle: tropism for Schwann cells or phagocytes; the resistance of the leprosy bacillus to intracellular killing; and immunomodulatory activities (18,50,14). However, analysis of the contribution of PGL-1 to the pathogenicity of M. leprae has been hampered by the failure of the bacterium to grow on laboratory media and its extremely slow growth in animal model.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that p-HBAD are present in the culture fluids of all the strains of M. tuberculosis examined raises the question of their role in virulence of the tubercle bacillus. These compounds are properly located to interact with host cells and contain the oligosaccharide moiety of PGL, which seems to be essential for the various acitivities found for the PGL of M. leprae (18,50,14). Once again the best way to address this question will be the generation and characterization of M. tuberculosis mutants devoid of p-HBAD.…”
Section: Discussionmentioning
confidence: 99%
“…The xanthine-xanthine oxidase system (23,24) was used to generate oxidants in vitro. Logarithmic-phase promastigotes were washed with PBS and suspended in 150 M xanthine in PBS at 5 ϫ 10 6 cells per ml, and 0.5-5 units of xanthine oxidase per ml of cells.…”
Section: Methodsmentioning
confidence: 99%
“…The most abundant constituent is a large GPI-anchored phosphoglycan called lipophosphoglycan (LPG) (2)(3)(4). In all Leishmania species, the GPI anchor of LPG is composed of a 1-O-alkyl-2-lysophosphatidylinositol lipid anchor and a heptasaccharide core, to which is joined a long phosphoglycan (PG) polymer composed of [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ] repeating units (substituted with other sugars in some species) and which is terminated by a capping oligosaccharide. These domains are shared with other molecules; the PG repeating units and caps occur on secreted proteins such as PPG or secreted acid phosphatase, and the core GPI anchor domains have similarities with those present in both GIPLs and GPI-anchored proteins (1,5,6).…”
mentioning
confidence: 99%
“…NO is reported to be microbicidal in vitro, which presumed to play a role in antimicrobial action. However, mycobacteria have developed the ability to resist ROI and RNI within the hostile environment of host phagocytes (32)(33)(34). In addition, NO represents as a crucial molecular signal, and we had previously reported that NO/iNOS-mediated regulation of proinflammatory gene expression involves multiple pathways in macrophages (18).…”
Section: Discussionmentioning
confidence: 99%